Targeted Metabolomics Shows That the Level of Glutamine, Kynurenine, Acyl-Carnitines and Lysophosphatidylcholines Is Significantly Increased in the Aqueous Humor of Glaucoma Patients - Lillo, Alejandro; Marin, Silvia; Serrano-Marín, Joan; Binetti, Nicolas; Navarro, Gemma; Cascante, Marta; Sánchez-Navés, Juan; Franco, Rafael (Frontiers in Medicine, 2022)
The composition of the aqueous humor of patients with glaucoma is relevant to understand the underlying causes of the pathology. Information on the concentration of metabolites and small molecules in the aqueous humor of healthy subjects is limited. Among the causes of the limitations is the lack of healthy controls since, until recently, they were not surgically intervened; therefore, the aqueous humor of patients operated on for cataract was used as a reference. Sixteen aqueous humor samples from healthy subjects undergoing refractive surgery and eight samples from glaucoma patients were used to assess the concentration of 188 compounds using chromatography and mass spectrometry. The concentration of 80 of the 188 was found to be reliable, allowing comparison of data from the two groups (glaucoma and control). The pattern found in the controls is similar to, but not the same as, that reported using samples from "controls" undergoing cataract surgery. Comparing data from glaucoma patients and healthy subjects, 57 of the 80 compounds were significantly (p<0.05) altered in the aqueous humor. Glutamine, but not glutamate, was significantly increased in the glaucoma samples. Furthermore, 10 compounds were selected considering a statistical score of p<0.0001 and the degree of change of more than double or less than half. The level of C10 (decanoyl)-carnitine decreased, while the concentration of spermidine and various acyl-carnitines and lysophosphatidylcholines increased in glaucoma. Principal component analysis showed complete segregation of controls and cases using the data for the 10 selected compounds. The receiver operating characteristic curve these 10 compounds and for glutamine allowed finding cut-off values and significant sensitivity and specificity scores. The concentration of small metabolites in the aqueous humor of glaucoma patients is altered even when they take medication and are well controlled. The imbalance affects membrane components, especially those of the mitochondria, suggesting that mitochondrial abnormalities are a cause or consequence of glaucoma. The increase in glutamine in glaucoma is also relevant because it could be a means of keeping the concentration of glutamate under control, thus avoiding its potential to induce the death of neurons and retinal cells. Equally ..the increase in kynurenine...